Prospective analysis of surfing and bodyboard injuries. (April 2019) - Dimmick, Simon; Gillett, Mark; Buchan, Craig; Sheehan, Patrick; Franks, Michelle; Ratchford, Andrew; Porges, Kate; Day, Robert; Milne, Tessa; Anderson, Suzanne
Objective: To assess the differences in the types of injuries sustained by surfboard and bodyboard riders and to identify common mechanisms of injury. Methods: Subjects were prospectively recruited to the study on presentation to one of the six hospital emergency departments. Consented subjects completed a questionnaire while in the emergency departments. Data regarding radiological investigations undertaken and their findings were collected retrospectively. Results: A total of 224 males and 28 females in the surfing group and 14 males in the bodyboard group were recruited. In surfers, the most common injured body parts were the head/face (115; 45.6%) and lower limb (69; 27.4%). Surfers were most commonly injured by a surfboard, either their own (178; 70.6%) or someone else's (18; 7.1%). Unfortunately, the small number of subjects recruited to the bodyboard group precluded meaningful comparison with the surfing group. Conclusions: The most common body part injured in surfers is the head/face compared with the lower limbs in bodyboard riders. Contact with a surfer's board (most commonly their own) is the most common cause of injury. Significant spinal fractures/injuries are sustained when the surfer (usually their head) strikes the seafloor. Head and facial fractures occur when the surfer is struck by their own board. Future research into surfboard design which incorporates softer compounds into the deck, rail, and fins is recommended. The need for local authorities and surf lifesavers to disseminate information relating to specific beaches to the general public regarding surf conditions, water depth, and the nature of the seafloor is also essential for injury prevention.